Validasi Data Model Prediksi Curah Hujan Satelit GPM, GSMaP, dan CHIRPS Selama Periode Siklon Tropis Seroja 2021 di Provinsi Nusa Tenggara Timur - Achmed Gerland; Aprilliani Ersa S Dengo; Yosafat Donni Haryanto (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2023)
Rainfall is also one of the meteorological parameters that are very influential in life. Measurements of this rainfall can also vary both from direct observations and remote sensing results from satellites. But often, data from satellites is not accurate for the conditions that occur in an area. The purpose of this study is to test the accuracy of product data from various GPM, GSMaP, and CHIRPS satellites with observational data using the Seroja tropical cyclone case study that will occur in 2021 in East Nusa Tenggara Province. Based on the results of the analysis, it can be seen that there are variations in various assessments, including RMSE, correlation, and contingency table analysis. In terms of correlation, it shows that the lowest correlation is in the Ruteng area based on data from the GSMaP satellite, and the highest correlation is in the Larantuka area based on data from the GSMaP satellite. Meanwhile, the satellite data that has the smallest error value is from the CHIRPS satellite data in the Maumere area.